2021
DOI: 10.1021/acs.macromol.1c01276
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Conjugated Micelles for Targeted Photodynamic Therapy Via Photoinitiated Polymerization-Induced Self-Assembly

Abstract: Here, we report photoinitiated polymerization-induced self-assembly (photo-PISA) mediated by Rose Bengal methacrylate (RBMA) to reproducibly construct nanoparticles in one pot, on a large scale, for photodynamic therapy (PDT). In this work, we take advantage of the multifunctionality of RBMA by applying the monomer as a photocatalyst for self-catalyzed PISA, a singlet oxygen (1O2) generator for PDT, and a fluorophore for imaging. Covalent incorporation of Rose Bengal (RB) into nanostructures by the polymerizab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…In 2021, Sumerlin et al reported a strategy to maximize the multifunctionality of Rose Bengal Methacrylate (RBMA) as both photocatalyst and comonomer in a photo-PISA process, also a singlet oxygen generator for PDT, and a fluorophore for imaging. 158 In their work, quantitative and controlled loading of Rose Bengal (RB) was realized by converting RB to the polymerizable methacrylate that could be covalently incorporated into nanoparticles. It was further demonstrated that RB-loaded nanoparticles can be activated by visible light, and the efficiency of singlet oxygen production was higher than free RB.…”
Section: Non-thermal Initiation Of Pisamentioning
confidence: 99%
“…In 2021, Sumerlin et al reported a strategy to maximize the multifunctionality of Rose Bengal Methacrylate (RBMA) as both photocatalyst and comonomer in a photo-PISA process, also a singlet oxygen generator for PDT, and a fluorophore for imaging. 158 In their work, quantitative and controlled loading of Rose Bengal (RB) was realized by converting RB to the polymerizable methacrylate that could be covalently incorporated into nanoparticles. It was further demonstrated that RB-loaded nanoparticles can be activated by visible light, and the efficiency of singlet oxygen production was higher than free RB.…”
Section: Non-thermal Initiation Of Pisamentioning
confidence: 99%
“…Korpusik et al [78] reported the design of a targeted micelle-based PDT system (Sgc8 micelles, hydrodynamic diameter of 52 nm) based on azide-functionalized polymeric micelles decorated with protein tyrosine kinase 7 (PTK7)-binding DNA (Deoxyribonucleic acid) aptamer (Sgc8) via click chemistry. The covalent conjugation of RB to micelles provided quantitative and controlled RB loading.…”
Section: Micelle Npsmentioning
confidence: 99%
“…The enhanced distribution lead to increased singlet oxygen production, creating a promising material for use in photodynamic therapy. 54…”
Section: Self-assembled Polymer Photocatalystsmentioning
confidence: 99%